Short term secular change in body size and physical fitness of youth 7–15 years in Southwestern Poland: 2001–2002 and 2010–2011 - Ignasiak, Zofia; Sławińska, Teresa; Malina, Robert M. (Anthropological Review, 2016)
Short term secular change in body size and physical fitness of Polish youth 7-15 years of age resident in an industrial region of Lower Silesia in southwestern Poland was considered across two surveys, 2001-2002 and 2010-2011. Subjects were students in the same schools in both surveys 1892 boys and 1992 girls in the first and 1237 boys and 1236 girls in the second. In addition to height and weight, performances in six fitness tests were measured in each survey. Height, weight and BMI increased significantly across surveys. Statistically controlling for secular gains in height and weight, only static strength (hand grip) and running speed - agility (shuttle run) improved significantly between surveys in three age groups (7-9, 10-12, 13-15 years), while explosive power (standing long jump) showed negligible changes except in girls 13-15 years among whom performances declined significantly. Speed of upper limb movement (plate tapping), flexibility (sit and reach) and trunk strength (sit-ups) declined between surveys, except for trunk strength in boys 13-15 years which did not change. In conclusion, after statistically controlling for secular gains in body size, physical fitness items changed variably over the decade.